Solve for t 3t-4=4(t+7)

Math
3t-4=4(t+7)
Simplify 4(t+7).
Tap for more steps…
Apply the distributive property.
3t-4=4t+4⋅7
Multiply 4 by 7.
3t-4=4t+28
3t-4=4t+28
Move all terms containing t to the left side of the equation.
Tap for more steps…
Subtract 4t from both sides of the equation.
3t-4-4t=28
Subtract 4t from 3t.
-t-4=28
-t-4=28
Move all terms not containing t to the right side of the equation.
Tap for more steps…
Add 4 to both sides of the equation.
-t=28+4
Add 28 and 4.
-t=32
-t=32
Multiply each term in -t=32 by -1
Tap for more steps…
Multiply each term in -t=32 by -1.
(-t)⋅-1=32⋅-1
Multiply (-t)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1t=32⋅-1
Multiply t by 1.
t=32⋅-1
t=32⋅-1
Multiply 32 by -1.
t=-32
t=-32
Solve for t 3t-4=4(t+7)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top